Conducting Hands-On Task in Vocational Education: Teaching Method in Automotive Courses - Ahmad, Adnan; Nordin, Mohd Khir; Ali, Dayana Farzeeha; Nabil, Ahmad (Journal of Technical Education and Training, 2015)
This paper discusses the findings from a study on teaching in practical work on automotive courses at Vocational Colleges in Malaysia. The random sampling technique was used in selecting 283 students and 63 teachers as respondents from the automotive courses. The findings of the research indicate that teachers have strong preference in using the demonstration and questioning technique during the set induction stage of teaching. Teachers also prefer group monitoring and problem solving during the teaching phase, and re-explaining and report writing in the post-teaching stage. This research provides the combination of teaching techniques that could be used in teaching vocational skills in general and automotive practical work in particular. This study has concluded that vocational teaching method in automotive practical work to be applied in teaching for other practical courses to improve current practices. Thus, teachers are proposed to use this method to improve students’ knowledge in automotive and to develop skills for the current and future workforce.